PENGEMBANGAN MEDIA SMART BOX TOKOH PEWAYANGAN TERINTEGRASI MODEL VCT UNTUK MENUMBUHKAN SIKAP NASIONALISME DALAM PENDIDIKAN PANCASILA SISWA KELAS 3 SD - Afrina Faizah; Mawardi (Universitas Negeri Medan, 2026)
This study aims to develop a Smart Box learning media based on wayang characters integrated with the Value Clarification Technique (VCT) model and to determine its validity, practicality, and effectiveness in fostering students’ nationalism attitudes. This research employed a Research and Development (R&D) method using the ADDIE model. The subjects consisted of 44 third-grade students. Data were collected through validation sheets, teacher and student response questionnaires, and a nationalism attitude scale. The results showed that the media achieved very high validity, with percentages of 96% (media), 86.6% (material), and 100% (instructional design). The effectiveness results indicated that 61.4% of students were in the very high category, 34.1% in the high category, and 4.5% in the moderate category, with no students in the low category. The practicality reached 96%, categorized as very high. Therefore, the media is valid, practical, and effective in fostering students’ nationalism attitudes.